Pergamon, Türkei: Die Arbeiten des Jahres 2015 - Pirson, Felix; Bachmann, Martin; Emme, Burkard; Erkul, Ercan; Herbrecht, Marina; Laufer, Eric; Mecking, Rebekka; Öztürk, Arzu; Pint, Anna; Rabbel, Wolfgang; Schwarz, Anja J.; Seeliger, Martin (e-Forschungsberichte des DAI, 2023)
The activities of the Pergamon-excavation in 2015 were part of the continuing research program on the urban organism of the Hellenistic residential city and on Pergamon´s countryside. The program also includes studies of the ancient necropolis and the natural sanctuaries as integral elements within the presentation of suburbs and hinterland. The campaign focused on (1) geophysical prospection and archaeological sondages at the monumental tumulus Yiğma Tepe, (2) the completion of the excavation within the alleged banquet-building at the northern east-slope, (3) the archaeological and architectural study of the Lower Agora, (4) the continuation and almost completion of the Kane-Peninsula (Kara Dağ) regional harbor survey, (5) the extensive conservation and restoration works at the Red Hall and the Gymnasion of Pergamon. A detailed preliminary report, which contains also information about other fields of activity such as palaeo-anthropology or dendrochronology, will be published in “Archäologischer Anzeiger” 2015/2.